The Use of Awabe’s English Pronunciation Application in Teaching Speaking - Utami, Anggitha Juliya; Regina; Wardah (JL3T (Journal of Linguistics, Literature and Language Teaching), 2024)
The necessity for effective tools to teach speaking skills to students remains essential due to the rapidly evolving landscape of language education. This article aims to assess the effectiveness of Awabe's English pronunciation application in teaching speaking, particularly segmental features pronunciation to the 8th grade students. Pre-experimental design with one group pre-test and post-test is used in this study. In the academic year 2023/2024, the target population consists of 98 eighth-grade students at SMP N 25 Pontianak, with a representative sample of 30 students selected from class 8C through cluster random sampling. Utilizing a pronunciation test as the primary data collection tool, the pre test mean score of 54.47 contrasts with the post-test mean score of 68.60. The statistical analysis, employing a t-test, yielded a significant result of 30.286 with a moderate effect size of 0.969, resulting in the null hypothesis’ rejection. These findings underscore the valuable contribution of Awabe's English pronunciation application, particularly emphasizing its impact on pronunciation in the teaching of speaking skills at the junior high school level. As English proficiency continues to be a crucial skill, this study advocates for the integration of this app in speaking skills instruction. Therefore, it was suggested that teachers utilize Awabe's English pronunciation application in teaching speaking, placing specific emphasis on pronunciation.